2021
DOI: 10.1093/mnras/stab2716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of massive binary star and cosmic evolution on gravitational wave observations I: black hole–neutron star mergers

Abstract: Mergers of black hole-neutron star (BHNS) binaries have now been observed by GW detectors with the recent announcement of GW200105 and GW200115. Such observations not only provide confirmation that these systems exist, but will also give unique insights into the death of massive stars, the evolution of binary systems and their possible association with gamma-ray bursts, r-process enrichment and kilonovae. Here we perform binary population synthesis of isolated BHNS systems in order to present their merger rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 380 publications
5
94
1
Order By: Relevance
“…is the probability of a successful jet launch in an NSBH merger (i.e., a Heaviside step function that evaluates to 0 when r disrupt > r ISCO ), and π(m NS , m BH , χ BH ) is the astrophysical distribution of neutron star and black hole masses and black hole spins of the components that participate in NSBH mergers. We calculate f s,BNS and f s,NSBH using the above prescription and a suite of results from Broekgaarden et al [28] that implements different population-synthesis prescriptions for the binary evolution physics-see that Paper, in particular their Tables 1 and 2, for a description of each of the models. From these various models, we take the mass distribution of neutron stars and black holes that participate in NSBH and BNS mergers and the orbital period before the second binary component explodes as a supernova, the latter informing the spin distribution of black holes that participate in NSBH mergers [28,44].…”
Section: A Jet-launching Fractionsmentioning
confidence: 99%
See 3 more Smart Citations
“…is the probability of a successful jet launch in an NSBH merger (i.e., a Heaviside step function that evaluates to 0 when r disrupt > r ISCO ), and π(m NS , m BH , χ BH ) is the astrophysical distribution of neutron star and black hole masses and black hole spins of the components that participate in NSBH mergers. We calculate f s,BNS and f s,NSBH using the above prescription and a suite of results from Broekgaarden et al [28] that implements different population-synthesis prescriptions for the binary evolution physics-see that Paper, in particular their Tables 1 and 2, for a description of each of the models. From these various models, we take the mass distribution of neutron stars and black holes that participate in NSBH and BNS mergers and the orbital period before the second binary component explodes as a supernova, the latter informing the spin distribution of black holes that participate in NSBH mergers [28,44].…”
Section: A Jet-launching Fractionsmentioning
confidence: 99%
“…We calculate f s,BNS and f s,NSBH using the above prescription and a suite of results from Broekgaarden et al [28] that implements different population-synthesis prescriptions for the binary evolution physics-see that Paper, in particular their Tables 1 and 2, for a description of each of the models. From these various models, we take the mass distribution of neutron stars and black holes that participate in NSBH and BNS mergers and the orbital period before the second binary component explodes as a supernova, the latter informing the spin distribution of black holes that participate in NSBH mergers [28,44]. We also marginalize over the unknown equation of state.…”
Section: A Jet-launching Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandel & Broekgaarden (2021) gave us a great summary on merger rates of compact object binaries, i.e., NS-NSs, BH-BHs and NS-BHs for GW observations and various formation channels. Using metallicity-specific star formation rate density prescriptions (Broekgaarden et al 2021b) in an isolated binary evolution scenario, Broekgaarden & Berger (2021) concluded that the observed two NS-BHs can be explained from this formation channel, and gave some constraint on the common envelope efficiency and the natal kick velocities of supernovae by treating BH-BHs and NS-NSs simultaneously. Taking the spin direction of BH of GW200115 into account, Fragione et al (2021) discussed this NS-BH in the evolution of isolated massive binary stars and effects 2021) have predicted that 16-40% events of short-duration gamma-ray burst will be hostless.…”
Section: Introductionmentioning
confidence: 99%